The development of a spatial decision support system to optimise agricultural resource use in the Western Cape - Pretorius, C. E. (Cornelia Elizabeth) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.